PENGELOLAAN PEMBELAJARAN MATEMATIKA DENGAN MENERAPKAN MODEL SIMULASI - Neti Herawati (Manajer Pendididikan, 2017)
The purpose of this research to know the student result towards the management of mathematics learning with the application of simulation models. The method used in this research was classroom action research.  The classroom action research directed to problems solving or to repairs the learning of process. The conclusion of the research was conducted encouraging for the group students of high, medium, and most of groups the less of the student ability to problems solve of mathematics test. Likewise the students interest towards the learning of mathematics shown by their efforts to complete the problem solving of mathematics story.